Фонетичні особливості Хітарського збірника І половини XVIII століття - Бичкова, Тетяна (ПП Данило С.І., 2023)
The article is a study of the phonetic phenomena found in the manuscript collection of the 1st half of the 18 th century from the village of Khitar, Stryi district. The manuscript was discovered and partly published by V. Hnatiuk (1897), and later I. Franko studied its content in his work “Carpatho-Ruthenian Writings of the 17 th –18th Centuries” (1900). However, it was not the object of linguistic research. The objective of the article is to analyze phonetic features of the Khitar collection, in particular those displaying the standardization of the Ukrainian phonetic system in the early 18th century. A number of common historically essential language phenomena which have become the norm of the Ukrainian literary language have been identified in the subsystem of vocalism: the change of *[ě] (ҍ) into [і]; the fusion of [і], [у] (ы) into [и]; the change of *[о], *[е] into [і] in the newly closed syllables; the transition of [e] into [o] after sibilants before historically hard consonants; the alternation у – в as a result of the change of [в] into [ў] and [у]. The study of consonantism has identified the most important phenomena indicative of the normalization of the phonetic system in the period under study: regressive assimilation based on voicing / voicelessness, the method and place of formation; progressive assimilation of the sound [j] by forelingual palatalized consonants; dissimilation of consonants; the change of [л] into [ў]; simplification in groups of consonants; epenthetic [j] and prothetic [в], [г] etc. However, quite often living language features are obscured by the Church Slavonic bookish orthographic tradition. Nevertheless, despite traditional orthography, the analyzed text clearly reflects not only common language phenomena, but also fundamental features of the south-western dialects (they often appear in parallel with those that have become the literary language norm), in particular the Boykos patois common in the territory where the Khitar manuscript was written. The fact that the features of dialect speech were noted in writing indicates the breaking of bookish traditions in the written literary practice of the time. However, patois features displayed in the text require a separate study. The analysis of phonetic features of the Khitar collection proves that in the 1st half of the 18 th century western Ukrainian territories underwent the living language processes common for the entire Ukrainian language area.
Phonetic features of the Khitar collection (1st half of the 18th century)
Keywords: фонетична система; вокалізм; консонантизм; південно-західне наріччя; бойківський говір; Хітарський збірник